O Sítio da patrimionial : uma análise sobre a outra faceta do bairro gênese da cidade de Belém - COSTA FILHO, Sidney Pery da Silva (2023)
This work aims to analyze the portion here designated as “the latter” of Cidade Velha neighborhood in Belém do Pará, which usually isn’t deservedly highlighted by architechture scientific productions due to the fact that the limits covered by the part chosen as the object of study doesn’t contain as much examples of buildings with interest to conservation as the ancient portion of the neighborhood. However, despite its differences from the older nucleus, the area has its importance. Through bibliographic research, photographic survey and the use of ethnographic method to conduct interviews with residents and heritage technicians, a historical contextualization of the area and the characterization of its architectural typologies and landscape were done. In addition, the different perceptions of the subjects who act, directly or indirectly, on the area were also presented. Thus, the study of this part of the neighborhood and the understanding about the existent dialogue between the newer and the ancient portion is necessary to make Cidade Velha be seen as a whole, which has multiple facets.